2004
DOI: 10.1002/mds.20351
|View full text |Cite
|
Sign up to set email alerts
|

Mutant torsinA, which causes early‐onset primary torsion dystonia, is redistributed to membranous structures enriched in vesicular monoamine transporter in cultured human SH‐SY5Y cells

Abstract: A single GAG deletion in the DYT1 gene causes primary early-onset, generalized torsion dystonia. The DYT1 protein product, torsinA, belongs to the AAA+ family of proteins. When overexpressed, wild-type torsinA localizes mainly to the endoplasmic reticulum, whereas the mutant forms inclusions of unclear biogenetic origin. In this study, overexpressed wild-type torsinA in human neuroblastoma (SH-SY5Y) cell lines was distributed throughout the cell body and colocalized with a marker for the endoplasmic reticulum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 28 publications
3
48
1
2
Order By: Relevance
“…The formation of membranous whorls caused by expression of ⌬E-torsinA is evident in E-cadherin-positive and SH-SY5Y transfected cells (7,14) but has been also observed in other non-neuronal cell lines overexpressing ⌬E-torsinA (data not shown). These inclusions appear to originate from the NE (47) and have been detected in DYT1 brain, supporting a role in the pathogenesis of dystonia (15).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The formation of membranous whorls caused by expression of ⌬E-torsinA is evident in E-cadherin-positive and SH-SY5Y transfected cells (7,14) but has been also observed in other non-neuronal cell lines overexpressing ⌬E-torsinA (data not shown). These inclusions appear to originate from the NE (47) and have been detected in DYT1 brain, supporting a role in the pathogenesis of dystonia (15).…”
Section: Discussionmentioning
confidence: 79%
“…Cell Culture-SH-SY5Y cell lines stably transfected with pcDNA3.1, containing either wild type DYT1, GAG-deleted DYT1 (DYT1-⌬E) or no insert (14) were grown in 1:1 mixture of Eagle's minimal essential medium (Promochem, Middlesex, UK), Ham's F-12 nutrient mixture (Invitrogen) and 10% fetal calf serum at 37°C and 5% CO 2 under selective conditions (0.4 mg/ml G418; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased DA turnover identified in hMT1 mice is noteworthy since tetrabenazine, a dopamine-depleting drug, has been used successfully in patients with generalized dystonia (Jankovic and Orman, 1988). Furthermore, mutant torsinA appears to interfere with the dopamine and vesicular monoamine transporters (Torres et al, 2004;Cao et al, 2005;Misbahuddin et al, 2005). Thus, the hMT1 mouse may be used to study the systems and cellular biology of torsinA and evaluate potential therapeutics for DYT1 dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Within neurons, wild-type torsinA localizes to the endoplasmic reticulum (Liu et al, 2003;Naismith et al, 2004;Hewett et al, 2007), while mutant torsinA protein is found in the perinuclear space (Hewett et al, 2000;Gonzalez-Alegre and Paulson, 2004;Goodchild and Dauer, 2004). Perhaps relevant to the topic of dopaminergic dysfunction to DYT1 dystonia, associations of mutant torsinA with the vesicular monoamine transporter (VMAT2) and with alphasynuclein have been described (Sharma et al, 2001;Misbahuddin et al, 2005).…”
mentioning
confidence: 99%